A NeoWicksellian in a new classical world: the methodology of Michael Woodford's Interest and Prices - Kevin D. Hoover (University of California, Department of Economics, 2004)
Woodford's Interest and Prices is considered from a methodological point of view. While innovative as a work of macroeconomic theory, it is decidedly in the mainstream methodologically. As such, it provides a good example of the methodological puzzles posed by modern macroeconomics: first, the notion that representative-agent models (or models with very constrained sorts of heterogeneous agents) provide genuine microfoundations; second, the idea that Paretian welfare economics in the context of such models gives any useful policy guidance.
Keywords: 330